Experiments indicating a second hydrogen ordered phase of ice VI. Issue 18 (5th April 2018) - Gasser, Tobias M.; Thoeny, Alexander V.; Plaga, Lucie J.; Köster, Karsten W.; Etter, Martin; Böhmer, Roland; Loerting, Thomas
Abstract : We report on the discovery and characterization of ice β-XV, which represents the second hydrogen ordered polymorph related to ice VI. Abstract : In the last twelve years five new ice phases were experimentally prepared. Two of them are empty clathrate hydrates and three of them represent hydrogen ordered counterparts of previously known disordered ice phases. Here, we report on hydrogen ordering in ice VI samples produced by cooling at pressures up to 2.00 GPa. Based on results from calorimetry, dielectric relaxation spectroscopy, Raman spectroscopy, and powder X-ray diffraction the existence of a second hydrogen ordered polymorph related to ice VI is suggested. Powder X-ray data show the oxygen network to be the one of ice VI. For the 1.80 GPa sample the activation energy from dielectric spectroscopy is 45 kJ mol −1, which is much larger than for the known hydrogen ordered proxy of ice VI, ice XV. Raman spectroscopy indicates the 1.80 GPa sample to be more ordered than ice XV. It is further distinct from ice XV in that it experiences hydrogen disordering above ≈103 K which is 26 K below the ice XV to ice VI disordering transition. Consequently, below 103 K it is thermodynamically more stable than ice XV, adding a stability region to the phase diagram of water. For the time being we suggest to call this new phase ice β-XV and to relabel it ice XVIII once its crystal structure is known.